An assessment of application of intelligence-driven investigation in the combating of organised vehicle theft in Thohoyandou Cluster - Bila, Hlengani Phanuel (My University, 2015)
The research concerned with the aim of this study, was to assess the appli-cation of intelligence-driven investigation in combating organised motor vehicle theft. The strategic intelligence plan, information sharing and understanding of or-ganised vehicle theft, are some of approaches which will assist in dealing with the challenge of the illegal sale of vehicles and vehicle parts. There is indeed a need to address police corruption, if the battle against vehicle theft is to be realised. The objectives of this study were the following: to explain the strategic intelli-gence plan for investigating motor vehicle theft; to evaluate whether investiga-tions of organised motor vehicle theft in Thohoyandou cluster are intelligence-driven; to assess if the cluster uses intelligence offender profiling in investi-gations; to explore how intelligence-driven investigation assists in information sharing; and, to make recommendations for the improvement of intelligence-driven vehicle theft investigation. The researcher wanted to apply new research knowledge, in order to develop good practice in the field. This has been done by recommending new proced-ures to enhance performance and to improve the ways and means of combating organised vehicle theft. KEY TERMS Intelligence-driven investigation; strategic intelligence; intelligence cycle; crime investigations; modus operandi; offender profiling; organised crime; systems theory; motor vehicle theft; information sharing.
Thesis (Ph.D. (Criminology)) -- University of Limpopo, 2015
Keywords: Intelligence-driven investigation; Strategic intelligence; Intelligence cycle; Crime investigations; Modus operand; Offender profiling; Organised crime; Systems theory; Motor vehicle theft; Crime prevention; Organised crime; Criminal behavior, Prediction of